Dance as a pedagogical and social practice for shaping life projects in the SENA Mosquera dance seedbed. (The Voz a Vos Bulletin, 2025)
This research, currently underway as part of the Master's Program in Performing Arts Education at the Antonio Nariño University, analyzes dance as a performance space in the development of life projects for young people at the SENA dance school in Mosquera. It is based on the premise that dance is not only an aesthetic practice, but also a pedagogical and social space where memory, identity, and processes of community transformation converge.The research question originates in the context of Mosquera, Cundinamarca, where urbanization and cultural homogenization have weakened traditional references, affecting youth participation in artistic expression. Given this situation, the question arises: how can dance, through the construction of performance spaces, contribute to the life projects of the students at the dance school, recognizing and highlighting the group's collective memory?The theoretical framework is based on categories such as the body as a living archive (Taylor, 2003), the constitutive imaginary (Castoriadis, 1975), collective memory (Ricoeur, 2000), critical pedagogy (Freire, 2005), and dance as a social and political practice (Schechner, 2002; Lepecki, 2006). Methodologically, a qualitative and participatory approach is proposed, integrating creative workshops, mapping exercises, and reflective journals.The results are expected to strengthen the understanding of dance as a tool for holistic development, memory, and social transformation.
Keywords: Dance; Collective Memory; Life project; Critical Pedagogy